ANALISIS DAMPAK PENYALURAN BANTUAN LANGSUNG TUNAI (BLT) DALAM PEMULIHAN PEREKONOMIAN MASYARAKAT AKIBAT - eka chyntia; Eko Gani PG; Mulia Andirfa (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Perppu No. 1 of 2020 provides a new instrument to minimize the impact of the Covid-19 pandemic on the village economy. Article 2 Paragraph (1) letter (i) of the regulation states that it is necessary to prioritize the use of budget allocations for certain activities (refocusing), adjustment of allocations, and/or cutting/delaying the distribution of budget transfers to regions and village funds, with certain criteria. Furthermore, in the explanation of the Perppu it is stated that what is meant by